АРХЕОЛОГИЙН СУДАЛГААНД ГЕОФИЗИКИЙН АРГЫГ АШИГЛАХ ТУРШИЛТ АРГА ЗҮЙН АЖЛЫН ТОВЧ ҮР ДҮН - Н.Арвисбаатар; С.Лантуу; Г.Батсүх (Mongolian Journal of Anthropology, Archaeology and Ethnology, 2002)
In this paper we have summarized the following conclusions by using the measured data of probing geophysical explorations carried out on a paleolit burials in the Uglugchiin herem, Eastern Mongolia. Because of the studying object's too small size we didn't observe a noticeable difference on a physical characteristics of the burial and its environment. In the right side, in distance of 2 m of the burial number 4 we observed some geophysical complex field anomal which might be generated by a possible archeological object. Usually there are no objects with enough size to generate a physical field to be detected by geophysical techniques. By this reason, the ultimate results of a geophysical exploration is being decreased. The sensitivity and precision of the used equipments were not sufficient to carry out such investigations, so we need more sensitive automated digital equipments.